2008
DOI: 10.1021/tx700347w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Protein Targets of 4-Hydroxynonenal Using Click Chemistry for ex Vivo Biotinylation of Azido and Alkynyl Derivatives

Abstract: Polyunsaturated fatty acids (PUFA) are primary targets of free radical damage during oxidative stress. Diffusible electrophilic R, -unsaturated aldehydes, such as 4-hydroxynonenal (HNE), have been shown to modify proteins that mediate cell signaling (e.g., IKK and Keap1) and alter gene expression pathways responsible for inducing antioxidant genes, heat shock proteins, and the DNA damage response. To fully understand cellular responses to HNE, it is important to determine its protein targets in an unbiased fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
270
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 189 publications
(273 citation statements)
references
References 57 publications
2
270
0
1
Order By: Relevance
“…Our preliminary experiments and other recent work (51) indicated that shotgun proteomic analysis of RKO cells exposed to lower HNE concentrations yielded far fewer protein target identifications. Use of higher HNE concentrations enabled detection of greater numbers of adducts, but the relative distributions of adducts should be largely independent of HNE concentration in the concentration range of our experiments.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Our preliminary experiments and other recent work (51) indicated that shotgun proteomic analysis of RKO cells exposed to lower HNE concentrations yielded far fewer protein target identifications. Use of higher HNE concentrations enabled detection of greater numbers of adducts, but the relative distributions of adducts should be largely independent of HNE concentration in the concentration range of our experiments.…”
Section: Discussionmentioning
confidence: 65%
“…Selective analysis of protein adducts requires an affinity capture method. Here we employed biotin hydrazide to label HNE adducts, but other approaches employing affinity postlabeling via Click chemistry or similar methods are certainly applicable (28,51,56). Although affinity capture enriches for adducted proteins, nonspecific binding of proteins to affinity-capture medium results in false positive target identifications.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Vila et al worked with alkynyl analogues of HNE to form adducts that can be label with azidobiotin tags by Cu + -catalyzed cycloaddition (Click chemistry), and they found that heat shock proteins 70 and 90, and the 78-kDa glucose-regulated protein, were selectively adducted [127]. While clearly a very effective approach to determining targets of HNE, unfortunately it cannot as yet be used to study the physiological occurrence of aldehydes in biological or clinical samples.…”
Section: Zhu Et Al Incubated Chymotrypsin Cytochrome C β-Lactoglobmentioning
confidence: 99%
“…Enrichment of HNE-modified proteins. Several of the approaches for the chemical enrichment of PCO-modified proteins can be applied for the identification of HNE modifications, such as biotin functionalized probes (98,275,392). For example, the biotin functionalized probe N¢aminoox-ymethylcarbonylhydrazino-D-biotin, also known as aldehydereactive probe, has been applied to identify HNE-modified proteins in human monocyte cell lines before and after ascorbic acid treatment (97).…”
Section: Fig 10 Outline Of Redox Proteomics Approachmentioning
confidence: 99%